2016
DOI: 10.4238/gmr.15038386
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microRNAs and their target genes associated with transcriptomic changes in gamma-irradiated Arabidopsis

Abstract: ABSTRACT. MicroRNAs (miRNAs) regulate gene expression in response to biotic and abiotic stress in plants. We investigated gammaray-responsive miRNAs in Arabidopsis wild-type and cmt3-11t mutant plants using miRNA microarray analysis. miRNA expression was differentiated between the wild-type and cmt3-11t mutants. miR164a, miR169d, miR169h, miR172b*, and miR403 were identified as repressible in the wild-type and/or cmt3-11t mutant in response to gamma irradiation, while miR827, miR840, and miR850 were strongly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The presence of DNA lesions influences miRNA degradation as well as their expression. In both plants and animals, it has been demonstrated that miRNAs are responsive to irradiation (IR)-induced oxidative stress and may be responsible for the post-transcriptional regulation of some DDR genes (Joly-Tonetti and Lamartine, 2012; Kim et al, 2016). Plant specific miRNAs responsive to genotoxic stress include the IR-induced Arabidopsis miR840 and miR850, which remain to be further characterized in terms of their roles in DDR and DNA repair (Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of DNA lesions influences miRNA degradation as well as their expression. In both plants and animals, it has been demonstrated that miRNAs are responsive to irradiation (IR)-induced oxidative stress and may be responsible for the post-transcriptional regulation of some DDR genes (Joly-Tonetti and Lamartine, 2012; Kim et al, 2016). Plant specific miRNAs responsive to genotoxic stress include the IR-induced Arabidopsis miR840 and miR850, which remain to be further characterized in terms of their roles in DDR and DNA repair (Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In both plants and animals, it has been demonstrated that miRNAs are responsive to irradiation (IR)-induced oxidative stress and may be responsible for the post-transcriptional regulation of some DDR genes (Joly-Tonetti and Lamartine, 2012; Kim et al, 2016). Plant specific miRNAs responsive to genotoxic stress include the IR-induced Arabidopsis miR840 and miR850, which remain to be further characterized in terms of their roles in DDR and DNA repair (Kim et al, 2016). Few rice miRNAs (osa-miR414, osa-miR164e, and osa-miR408) demonstrated to target specific helicases (Macovei and Tuteja, 2012) were also found to be responsive to γ-irradiation (Macovei and Tuteja, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Histone trimethyltransferases and/or acetyltransferases may induce histone modifications associated with the transcription of some DDR genes in Arabidopsis after γ-irradiation [78]. In addition, small noncoding microRNAs (miRNAs) in plant and animal genomes are responsive to IR-induced oxidative stress and may be responsible for the epigenetic regulation of some DDR genes [79,80]. The specific roles of plant epigenetic modifiers in DNA damage signaling and repair are detailed in Section 5.2, Section 5.3 and Section 5.4.…”
Section: Epigenetic Regulation For Dna Damage Signaling and Repairmentioning
confidence: 99%
“…However, there is no direct evidence supporting a correlation between miRNAs and DDR/DNA repair in plants. Plant specific and genotoxic stress-responsive miRNAs including the IR-induced Arabidopsis miR840 and miR850 remain to be further characterized in terms of their functions in DDR and DNA repair [80].…”
Section: Chromatin and Epigenetic Modifiers For Ddrmentioning
confidence: 99%